Mecanismos envolvidos no aumento da concentração plasmática de Sb a partir das composições de antimoniato de meglumina com ciclodextrina, visando o tratamento oral das leishmanioses - Patricia Silveira Martins (2007)
Meglumine antimoniate (MA), complex of pentavalent antimony (Sb(V)) with Nmethyl-D-glucamine (NMG), is currently an agent of choice for the treatment of leishmaniases. This compound is considered inactive when given enterally and is subject to rapid renal clearance after parenteral administration, requiring a multiple dosing regimen. Recently, it was reported that the association of MA to ß-cyclodextrin (ß-CD) enhances the oral absorption of Sb and renders this drug active by the oral routein a model of cutaneous leishmaniasis. However, since MA is highly water-soluble and, most probably, does not interact with the internal hydrophobic cavity of ß-CD, the mechanism responsible for the enhanced oral absorption of Sb in the MA/ß-CD composition is expected to differ from that involved in conventional inclusion drug/ß-CD complexes. The main objective of the present thesis was to investigate the mode ofaction of the MA/ß-CD composition. For that, MA and the MA/ß-CD composition were physicochemically characterized and their oral absorption in mice and their permeation across a lipid bilayer model were investigated. Since the preparation of MA/ß-CD composition consists in a two-step process, involving the heating of an equimolar MA +ß-CD mixture at 55oC for 48 h followed by the freeze-drying of the mixture, the effects of heating and of freeze-drying on the physicochemical characteristics of the resulting composition were evaluated. Osmolarity measurements and ESI mass spectrometry analyses of aqueous MA solutions and equimolar MA/ß-CD mixture indicated that theheating step induces the dissociation of MA into species of low molecular weight (1:1Sb-NMG complex) and the formation of ternary NMG-Sb-ß-CD complexes. Circular dichroism and ESI mass spectrometric analyses showed that the freeze-drying step promotes multiple associations between MA and ß-CD, including the formation of (NMG-Sb)2-ß-CD and (NMG-Sb-CD)2 complexes. Oral absorption of Sb in mice from MA+ß-CD physical mixture, heated MA/ß-CD and heated and freeze-dried MA/ß-CDindicated that the heating process increases by less than 2-fold Sb concentration in the serum of mice, while the freeze-drying step enhances significantly by 2- to 3-fold the Sb level. A lipid bilayer model, consisting of glutathione (GSH)-containing liposomes made from phosphatidylcholine, was developed in order to evaluate the permeation of Sb(V) across the lipid bilayer. This model allowed the determination of the permeability coefficient of antimoniate. Its value was found to be equal to 0.82 x 10-10 cm s-1, which is close to the value reported for Cl- ion. The comparison between the permeation rates of MA and of MA/ß-CD composition did not show significant difference under the conditions of concentration and temperature used in this model. A circular dichroismexperiment indicated that the MA/ß-CD composition acts as a sustained release system of the antimonial drug, MA. Since cyclodextrins are poorly digested in the small intestine, the association of MA with ß-CD may change the drug absorption site. In addition to the new insights achieved into the mode of action of the MA/ß-CD composition, the present work led us to propose also two new formulations for the oral administration of Sb: one which consists in pre-heated MA and is potentially less toxicand of lower cost, when compared to MA/ß-CD compositions; the other which consists in a MA/ß-CD composition, exhibits a higher solubility in comparison to 1:1 MA/ß-CD composition and is potentially less toxic and of lower cost.